Pengenalan Sistem Reproduksi Laki-Laki Pada Anak Sekolah Dasar Di SDIT MGI Ciamis - Lusi Lestari; Sri Wulan Ratna Dewi; Neli Sunarni; Resna Litasari (LPPM STIKes Muhammadiyah Ciamis, 2026)
Introduction: Early reproductive health education is an important aspect of improving children's understanding of the body, biological functions, and self-protection. However, the persistence of taboos in society leads to low knowledge of the reproductive system among elementary school children. This community service aims to improve students' knowledge and understanding of the male reproductive system, awareness of maintaining reproductive organ hygiene, and understanding of body boundaries as an effort to prevent sexual violence. Objective: This community service aims to improve students' knowledge and understanding of the male reproductive system, awareness of maintaining reproductive organ hygiene, and understanding of body boundaries as an effort to prevent sexual violence. Method: This activity uses a descriptive design with a participatory educational approach involving 17 students aged 9-10 years at SDIT MGI Ciamis. The methods used include interactive lectures and demonstrations with learning media in the form of props (phantoms). Result: The results showed a significant increase in the average score from 65 (pre-test) to 85 (post-test), which indicates the effectiveness of the demonstration method in improving students' understanding. Qualitatively, students showed high enthusiasm, active participation, and increased awareness of the importance of maintaining body hygiene and boundaries. Thus, reproductive system education through an interactive and age-appropriate approach has proven effective in improving students' knowledge and positive attitudes. Conclusion: Reproductive system education through an interactive, age-appropriate approach has proven effective in increasing students' knowledge and positive attitudes. This activity recommends the ongoing integration of reproductive health education into the elementary school curriculum as a promotional and preventive measure against health risks and sexual violence toward children.